2018
DOI: 10.2147/ppa.s172021
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction survey among primary health care outpatients in the backward region: an empirical study from rural Western China

Abstract: BackgroundWith a growing health demand, patient satisfaction analysis is essential for evaluating the accessibility and performance of medical services. Previous studies had explored the Chinese outpatient satisfaction and influencing factors in developed areas and tertiary hospitals. Considering the lower education level, less income, and heavier economic burden, it was necessary to conduct a region-specific questionnaire survey for the outpatient’s satisfaction in rural Western China.ObjectiveTo analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 33 publications
7
23
0
Order By: Relevance
“…In line with previous studies, elderly people were more satisfied with health care services compared to younger people, although contradictory results have also been found [ 7 9 , 20 ]. Older people might consider their illness and treatments a burden [ 15 ], and dissatisfied elderly patients are more likely to be chronically ill [ 14 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with previous studies, elderly people were more satisfied with health care services compared to younger people, although contradictory results have also been found [ 7 9 , 20 ]. Older people might consider their illness and treatments a burden [ 15 ], and dissatisfied elderly patients are more likely to be chronically ill [ 14 ].…”
Section: Discussionsupporting
confidence: 88%
“…The patient's perceptions, previous experiences, and fulfilment of expectations influence health care satisfaction [7,8]. Relevant factors affecting patient satisfaction include the population's demographic characteristics, health status, and chronic illnesses [7,[9][10][11][12][13][14][15][16][17][18]. Among the Finnish population, multimorbidity is rising [19].…”
Section: Introductionmentioning
confidence: 99%
“…A study from rural western China showed that patients in primary healthcare were relatively less satisfied with medical services than developed areas. 49 Our study may have indicated this too.…”
Section: Patients' Characteristicsmentioning
confidence: 75%
“…Moreover, hospitals in a less developed area may face a larger proportion of patients with a lower education level. 49 They may have more demands of medical knowledge. However, with such a workload, nurses were eager to educate patients and therefore provide incomplete information that could not meet patients' needs.…”
Section: Patients' Characteristicsmentioning
confidence: 99%
“…61 Due to the shortage of health resources, barefoot doctors with low-educational level and informal identity recognition still served as community health workers in the rural areas, 62 which accounted for some complaints in the study about their incompetent professional. 63 Besides, owning less awareness to seek appropriate selfmanagement strategies, people in such areas were easily trapped in a health-product sale scheme. 64 Cultural setting, including cuisines culture, traditional norms, and values, is another implication that should be highlighted.…”
Section: Discussionmentioning
confidence: 99%